Penerapan Model Pembelajaran Discovery Learning Muatan Matematika Sebagai Upaya Meningkatkan Hasil Belajar Siswa Di Kelas IV SDN 137/IX Petaling - Suyanto Suyanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This research aims to obtain information and discuss the Implementation of Discovery Learning Model of Mathematics Content as an effort to improve student learning outcomes in Grade IV SDN 137/IX Petaling. This type of research is class action research. This research was conducted at SDN 137/IX Petaling in the even semester of the 2018/2019 school year. The subjects in this study were grade IV students of SDN 137/IX Petaling with a total of 28 students with a male number of 18 men and 10 women. These research procedures include planning, implementation, observation, and reflection. The study was conducted in two cycles, each cycle consisting of two meetings. Techniques used in data collection are observations, tests, field records and documentation. Data is analyzed through percentage and data reduction. The results of this study show that the results of students' mathematics content in the learning process improved by using discovery learning models with the act of giving praise.